2021
DOI: 10.1093/cid/ciab334
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Direct-Acting Antiviral Treatment Adherence Patterns and Sustained Viral Response Among People Who Inject Drugs Treated in Opioid Agonist Therapy Programs

Abstract: Background Adequate medication adherence is critical for achieving sustained viral response (SVR) of hepatitis C virus (HCV) among people who inject drugs (PWID). However, it is less known which patterns of direct-acting antiviral (DAA) treatment adherence are associated with SVR in this population or what factors are associated with each pattern. Methods The randomized three-arm PREVAIL study utilized electronic blister pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…Other studies in PWUD and the homeless have also reported non-adherence to be associated with non-SVR12. [28][29][30] However, since adherence was self-reported in our study, we accept that this may have underestimated the severity of non-adherence. Use of OAT was also a predictor of SVR12 in our study.…”
Section: Univariate Analysismentioning
confidence: 99%
“…Other studies in PWUD and the homeless have also reported non-adherence to be associated with non-SVR12. [28][29][30] However, since adherence was self-reported in our study, we accept that this may have underestimated the severity of non-adherence. Use of OAT was also a predictor of SVR12 in our study.…”
Section: Univariate Analysismentioning
confidence: 99%
“… 33 Among those taking only DAAs, overall adherence, consecutive days of doses taken or missed, and adherence in the first 4 and 8 weeks of treatment (but not weeks 8–12) were associated with SVR. 34 …”
Section: Electronic Blister Packsmentioning
confidence: 99%
“…33 Among those taking only DAAs, overall adherence, consecutive days of doses taken or missed, and adherence in the first 4 and 8 weeks of treatment (but not weeks 8-12) were associated with SVR. 34 Electronic pill boxes Electronic pill boxes, such as the Wisepill ® RT2000 (Cape Town, South Africa), 35 are reusable compartmented pill boxes that wirelessly monitor opening of the outer pill box portion (Figure 4). 35 These are equipped with a SIM card connected to a cellular network and are battery powered.…”
Section: Electronic Blister Packsmentioning
confidence: 99%
“…The PREVAIL study 2 was conducted in opioid treatment program (OTP) settings to test the effectiveness of three models of HCV care for PWID. The trial showed that higher adherence was associated with successful SVR and the adherence level was highest among participants treated with modified directly observed therapy (mDOT) compared to those treated with groups therapy (GT) or standard individual therapy (SIT) 7 . We examined whether more intensive care models such as mDOT or GT would also increase adherence even among participants with active drug use compared to those without at baseline and during treatment.…”
Section: Introductionmentioning
confidence: 99%